Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.2 - Multiplying and Dividing Rational Expressions - Exercise Set: 27

Answer

$\dfrac{x+2}{7-x}\div\dfrac{x^{2}-5x+6}{x^2-9x+14}=\dfrac{x+2}{3-x}$

Work Step by Step

$\dfrac{x+2}{7-x}\div\dfrac{x^{2}-5x+6}{x^2-9x+14}$ Factor the second fraction completely: $\dfrac{x+2}{7-x}\div\dfrac{x^{2}-5x+6}{x^2-9x+14}=\dfrac{x+2}{7-x}\div\dfrac{(x-2)(x-3)}{(x-2)(x-7)}=...$ Evaluate the division of the two rational expressions: $...=\dfrac{(x+2)(x-2)(x-7)}{(7-x)(x-2)(x-3)}=...$ Simplify by removing repeated factors in the numerator and the denominator. To remove $(x-7)$ and $(7-x)$, change the sign of the factor $(7-x)$ and change the sign of the fraction: $...=\dfrac{(x+2)(x-7)}{(7-x)(x-3)}=-\dfrac{(x-7)(x+2)}{(x-3)(x-7)}=-\dfrac{x+2}{x-3}=\dfrac{x+2}{3-x}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.